RAD9-dependent G1 arrest defines a second checkpoint for damaged DNA in the cell cycle of Saccharomyces cerevisiae. - Siede, W (1993)
Exposure of the yeast Saccharomyces cerevisiae to ultraviolet (UV) light, the UV-mimetic chemical 4-nitroquinoline-1-oxide (4NQO), or gamma radiation after release from G1 arrest induced by alpha factor results in delayed resumption of the cell cycle. As is the case with G2 arrest following ionizing radiation damage [Weinert, T. A. & Hartwell, L. H. (1988) Science 241, 317-322], the normal execution of DNA damage-induced G1 arrest depends on a functional yeast RAD9 gene. We suggest that the RAD9 gene product may interact with cellular components common to the G1/S and G2/M transition points in the cell cycle of this yeast. These observations define a checkpoint in the eukaryotic cell cycle that may facilitate the repair of lesions that are otherwise processed to lethal and/or mutagenic damage during DNA replication. This checkpoint apparently operates after the mating pheromone-induced G1 arrest point but prior to replicative DNA synthesis, S phase-associated maximal induction of histone H2A mRNA, and bud emergence.